Identification of the cDNA Encoding the Growth Hormone Receptor (GHR) and the Regulation of GHR and IGF-I Gene Expression by Nutritional Status in Reeves’ Turtle (Chinemys reevesii) - Zhu, Wenlu; He, Yuhui; Ruan, Zhuohao; Zhang, Xiquan; Liao, Liangyuan; Gao, Yicong; Lin, Nani; Chen, Xiancan; Liang, Rui; Liu, Wen-sheng (Frontiers in Genetics, 2020)
Chinemys reevesii is a slow-growing reptile that is distributed widely in China. At present, we are still unclear about the cDNA sequence of Chinemys reevesii growth hormone receptor gene. Moreover, we know little about the gene expression change of the growth hormone receptor and growth hormone-insulin-like of the turtle under starvation. In this study, we identified the full length sequence of the GHR cDNA by using RT-PCR and RACE. The full-length of GHR cDNA consists of 3936 base pairs with an 1848-base-pair open reading frame, encoding 615 amino acids in Chinemys reevesii. GHR mRNA was found in a wide array of tissues with the highest expression in the liver, the lowest in gonad. On the other hand IGF-I also expressed in various tissues except in gonad, and highest on liver. After four weeks of fasting, the expression levels of GHR and IGF-I gene in the liver were significantly decreased. The expression levels of these genes gradually returned to normal after refeeding. However, we cloned the cDNA sequence of the turtle GHR gene for the first time, which is helpful to clarify the function of the turtle GHR gene. We also provide a reference for studying the effects of different nutrient levels on GHR gene expression in Chinemys reevesii.